Phase management of low-reactivity fuel in methanol/diesel RCCI combustion: comparative assessment of thermal vaporisation and ultrasonic atomisation - Ozturk, Gokhan; Firat, Mujdat (Pergamon-Elsevier Science Ltd, 2026)
This study investigates three different methods for introducing methanol, a LRF, into the intake manifold within a methanol/diesel RCCI combustion strategy. The tested approaches were conventional liquid-fuel port injection (C-RCCI), ultrasonic atomisation-assisted port injection (U-RCCI), and thermal vaporisation with vapour-phase injection (T-RCCI). Tests were performed at a constant speed of 2500 rpm and an injection pressure of 350 bar, with engine loads set at 25%, 50%, and 75% and cycle-based premixing ratios of 15%, 30%, and 45% on an energy basis. The results confirm that RCCI combustion can significantly reduce smoke emissions compared with conventional diesel operation. At the most critical condition, 75% load and Rp = 45%, smoke opacity decreased by 89% in C-RCCI, 87% in U-RCCI, and 79% in T-RCCI. However, the methods showed differences in combustion intensity and stability. U-RCCI produced the strongest premixed combustion behavior, leading to the highest rise in in-cylinder pressure and temperature. At 75% load and Rp = 45%, the maximum pressure increase reached 21.8% in U-RCCI, compared with 14.8% in C-RCCI and 11.5% in T-RCCI. Similarly, the maximum temperature increase was 15.2% in U-RCCI, while T-RCCI limited it to only 4.7%. In terms of emissions, T-RCCI offered the most balanced performance. Although methanol RCCI generally tends to increase CO and HC emissions, T-RCCI significantly reduced these drawbacks. At Rp = 45%, it lowered CO emissions by 18-71% and HC emissions by 47.6-68.6% relative to C-RCCI. Overall, T-RCCI appears the safest and most effective method, providing high smoke reduction while limiting knock tendency and incomplete oxidation.
Keywords: Thermal Vaporisation; Ultrasonic Atomisation; Methanol; Rcci; Phase-Controlled Combustion; Low-Carbon Fuel